Microbiological Characterization of Vertebral and Joint Infections and their Radiological Signatures on Gadolinium-Enhanced MRI - Nhaer , Ahlam Gareeb; Resen , Imad kh.; Muslim , Waleed Mahdi (American Journal of Biology and Natural Sciences, 2025)
Background: Infections such as osteomyelitis, discitis, and septic arthritis continue to pose significant diagnostic challenges, even in modern medicine. These conditions can often mimic one another and target various areas within the musculoskeletal system. The primary difficulty lies in their subtle symptoms, coupled with the fact that standard microbiological tests frequently fail to provide definitive answers. Over time, gadolinium-enhanced MRI (Gd-MRI) has evolved beyond a mere imaging technique; it now serves as a valuable tool for gaining insights into inflammatory processes that were previously difficult to detect. However, we are only beginning to grasp how the findings from Gd-MRI correspond with microbial data and systemic markers such as CRP or ESR. Objective: The purpose of this study is to see if Gd-MRI can identify microbiological and serological indicators in different patient groups, along with imaging infections. We want to see how well each patient's medical history and cultures, CRP, ESR, and Gd-MRI correspond to biological reality. Methods: Over five months, we tracked 120 Iraqi patients—men and women of various ages, immune conditions, and everyday routines—all suspected of having musculoskeletal infections. Each patient underwent Gadolinium-enhanced MRI, along with PCR, cultures, and inflammation lab tests. But we did not stop there. We also tried to figure out how factors like smoking, gender, and even a history of COVID-19 would influence the findings. It was not always straightforward. To bridge the clinical and imaging gaps, we calculated common diagnostic values (sensitivity, specificity)., PPV, and NPV—and used kappa agreement to check how much our imaging findings actually matched the biological reality underneath. Results: On MRI, we noticed disc enhancement in about 28% of patients, and epidural or paraspinal abscesses in roughly 32%. These patterns, in many cases, lined up surprisingly well with microbiology results. Interestingly, Gram stain and aerobic cultures came back positive in 37.5% and 43.3% of cases, but PCR helped uncover several infections that cultures had missed altogether. When we compared MRI with microbiology, the strongest links appeared in cases with disc enhancement (82.3%) and epidural abscesses (84.2%). Gadolinium-enhanced MRI turned out to be quite sensitive—86.7%—with a specificity of around 73.3%. CRP was elevated in 80% of patients, even in some who had no visible microbes on culture, which was telling. One thing that stood out was how MRI became harder to read—and cultures went silent—among smokers and people who had recovered from COVID-19. That made us realize: the immune system doesn’t always follow a textbook. Conclusion: Gadolinium-enhanced MRI is more than just a scanner; it is also a translator of inflammation, particularly when serology or cultures fail. Gd-MRI enables clinicians to act not based on guesswork but rather on the basis of multifaceted, convergent evidence in conjunction with microbiological and serological findings, even in settings with limited resources. This study pushes us to think of diagnosis as a dialogue between images, microbes, and molecules—and the human bodies in which they reside—rather than as a single answer.